Efektivitas Water Tepid Sponge Suhu 37°C Dan Kompres Hangat Suhu 37°C Terhadap Penurunan Suhu Pada Anak Dengan Hipertermia - Anggraeni Beti Dwi Lestari; Bambang Sarwono; Adi Isworo (Prodi Keperawatan Purwokerto, 2019)
Background: Most of the fever that occurs in children results from changes in the heat center (thermoregulation) in the hypothalamus. The results of a preliminary study conducted at the Dahlia Children's Ward of Tidar City Hospital, Magelang, that there were 326 children with fever in November 2018-January 2019 and in January 2019 there were 123 children. The action taken at the Tidar City Hospital in Magelang if the child has a fever is the administration of antipyretics and warm compresses. Objective: To determine the effectiveness of water tepid sponge at 37 ° C and warm compresses at 37 ° C for temperature reduction in children with hyperthermia. Method: Quantitative research type, Quasi Experimental research design with Non Equivalent Control design, which is an experiment where the observation is done twice, namely before (Pre Test) and after experiment (Post Test). Analysis using univariate and bivariate with Mann Whitney test. Results: Analysis of data using the Mann Whitney test results were p = 0.001 (p 0.1). Conclusion: This study concludes that Water Tepid Sponge is more effective in lowering body temperature in children with hyperthermia.